1998
DOI: 10.1098/rspb.1998.0378
|View full text |Cite
|
Sign up to set email alerts
|

Population differences in spatial learning in three–spined sticklebacks

Abstract: In a changing environment, learning and memory are essential for an animal's survival and reproduction. The role played by the environment in shaping learning and memory is now attracting considerable attention. Until now, studies have tended to compare the behaviour of two, or at best a few species, but interspeci¢c comparisons can be misleading as many life history variables other than environment may di¡er between species. Here we report on an experiment designed to determine how learning varies between di¡… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 16 publications
(18 reference statements)
3
95
1
Order By: Relevance
“…Blue and yellow 'L-shaped' walls were placed in the back corners of each test tank to create two chambers, each with a single entrance (see the electronic supplementary material). Because we were interested in assessing learning rather than colour per se, the blue chamber always contained the food reward (bloodworm-filled Petri dish) [14]. We alternated the tank side with the blue chamber between trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blue and yellow 'L-shaped' walls were placed in the back corners of each test tank to create two chambers, each with a single entrance (see the electronic supplementary material). Because we were interested in assessing learning rather than colour per se, the blue chamber always contained the food reward (bloodworm-filled Petri dish) [14]. We alternated the tank side with the blue chamber between trials.…”
Section: Methodsmentioning
confidence: 99%
“…We used a discrimination learning protocol known to be effective in stickleback [14]. Blue and yellow 'L-shaped' walls were placed in the back corners of each test tank to create two chambers, each with a single entrance (see the electronic supplementary material).…”
Section: Methodsmentioning
confidence: 99%
“…Feeders consisted of columns (5 cm  5 cm  35 cm high) with opaque sides and a transparent front (van Bergen et al 2004). To facilitate learning, one feeder was coloured blue and the other yellow (Girvan & Braithwaite 1998), although which colour of feeder was designated 'rich' or 'poor' (see below) was balanced within experimental groups. A pilot experiment confirmed that fish showed no prior preference for either colour of feeder (binomial test: n ¼ 20, p ¼ 0.82).…”
Section: Methodsmentioning
confidence: 99%
“…More generally, we 337 suggest that the use of learning speed as a measure of cognitive ability without consideration of the 338 types of strategies animals might employ given their past experiences and the conditions at test might 339 lead to erroneous conclusions (Girvan and Braithwaite 1998;Chittka et al 2009;Ducatez et al 2014). 340…”
Section: ------Insert Figure 1 ------275 276mentioning
confidence: 93%